Do selfing species have greater niche breadth? Support from ecological niche modeling. (28th November 2019) - Grant, Alannie‐Grace; Kalisz, Susan
Abstract: We explore the relationship between plant mating system (selfing or outcrossing) and niche breadth to gain new insights into processes that drive species distributions. Using a comparative approach with highly selfing versus highly outcrossing sister species, we test the extent to which: (1) species pairs have evolved significant niche divergence and less niche overlap, (2) selfers have wider niche breadths than outcrossers or vice versa, and (3) niches of selfers and outcrossers are defined by significant differences in environmental variables. We applied predictive ecological niche modeling approaches to estimate and contrast niche divergence, overlap and breadth, and to identify key environmental variables associated with each species' niche for seven sister species with divergent mating systems. Data from 4862 geo‐referenced herbarium occurrence records were compiled for 14 species in Collinsia and Tonella (Plantaginaceae) and 19 environmental variables associated with each record. We found sister species display significant niche divergence, though not as a function of divergence time, and overall, selfers have significantly wider niche breadths compared to their outcrossing sisters. Our results suggest that a selfing mating system likely contributes to the greater capacity to reach, reproduce, establish, and adapt to new habitats, which increases niche breadth of selfers.